Pengaruh Penggunaan Platform E-Commerce dan Digital Payment Terhadap Perilaku Konsumtif pada Generasi Z di Era Revolusi Industri 4.0: Studi Kasus Kota Pematang Siantar - Nurul Hafizah; Zuhrinal M. Nawawi; Mawaddah Irham (Masyarakat Ekonomi Syariah Bogor, 2026)
The purpose of this study was to determine the effect of e-commerce and digital payment platform usage on consumer behavior among Generation Z in Pematang Siantar City during the Industrial Revolution 4.0 era. This study used a quantitative approach. Data collection was conducted using a questionnaire with 100 respondents. The use of e-commerce and digital payment contributed 37.8% to consumer behavior, with the remaining 62.2% explained by other variables outside the research model. The t-test results concluded that e-commerce and digital payment variables had a positive and significant effect on consumer behavior among Generation Z in Pematang Siantar City during the Industrial Revolution 4.0 era. Based on the ANOVA test, the calculated F-value was 28.907, which was greater than the F-table (2.47). It can be concluded that the use of e-commerce and digital payment platforms simultaneously influenced consumer behavior among Generation Z in Pematang Siantar City during the Industrial Revolution 4.0 era.